PENGARUH GAYA KEPEMIMPINAN, LINGKUNGAN KERJA DAN KOMPENSASI TERHADAP KINERJA PEGAWAI - Dameria Hijryanthi Serka; Elfrida Viesta Napitupulu (Jurnal Ilmiah Hospitality, 2022)
Employee performances are measured by comparing them with the predetermined standards that have been set by the company. The purpose of this study was to determine the effect of leadership style, work environment and remuneration on employee performances at KPP Madya Jakarta Utara. The research method used is saturated sampling technique by collecting data through questionnaires distributed to 110 (one hundred and ten) respondents, which is the total number of employees of the KPP Madya Jakarta Utara. The measuring instruments in this research are outer model and inner model. The tool used is Smart PLS. The results of the study indicate that leadership style has a positive and significant impact on employee performances, work environment has a positive and significant impact on employee performances and remuneration has a positive and significant impact on employee performances.